Nickel Electrodeposition on Silver for the Development of Solid Oxide Fuel Cell Anodes and Catalytic Membranes - Jamil,Z; Ruiz-Trejo,E; Brandon,NP (Journal of The Electrochemical Society, 2017)
Nickel was electrodeposited on porous Ag/GDC (silver/Ce0.9Gd0.1O2-x) scaffolds and dense Ag/GDC composites for the fabricationof SOFC electrodes and catalytic membranes respectively. To control the distribution and amount of nickel deposition on the Ag/GDCsurfaces; first, a systematic cyclic voltammetry study of nickel electrodeposition from a Watts bath on silver foils was carried outto understand the influence of operating conditions on the electrodeposition process. From the cyclic voltammetry study, it can beconcluded that suitable operating conditions for nickel electrodeposition into porous Ag/GDC scaffolds and catalytic membranesare: 1.1 M Ni2+ concentration in Watts bath; deposition potential between −0.65 to −1.0 V vs. Ag/AgCl; a temperature at 55C;sodium dodecyl sulfate (SDS) as the surfactant; pH 4.0 ± 0.2 and an agitation rate of 500 rpm. It was observed that the nickel surfacemicrostructure changed with the deposition current densities due to the co-evolution of H2. Pulse and continuous electrodepositionmodes allow nickel to be deposited throughout porous Ag/GDC scaffolds and onto catalytic membranes. The pulse electrodepositionmode is favored as this is shown to result in an even Ni distribution within the porous scaffolds at minimum H2 pitting.